Development and Validation of a Novel LC-MS/MS Method for a TDM-Guided Personalization of HSCT Conditioning with High-Dose Busulfan in Children - Alessia Cafaro; Federica Pigliasco; Giammarco Baiardi; Sebastiano Barco; Manuela Stella; Roberto Bandettini; Francesca Mattioli; Maura Faraci; Giuliana Cangemi (Biomedicines, 2023)
Personalization of busulfan (Bu) exposure via therapeutic drug monitoring (TDM) is recommended for patients treated with high-dose conditioning regimens. Several laboratories’ developed methods are available in the literature with a lack of standardization. The aim of this study is to develop a new standardized LC-MS/MS method and validate it according to the international ICH M10 (EMA) guidelines. Our method is based on rapid protein precipitation from 50 µL plasma followed by separation on a reversed-phase C-18 UHPLC column after the addition of deuterated internal standard and has been tested on real samples from pediatric patients treated with myeloablative conditioning regimens, including Bu, before autologous or allogeneic hematopoietic stem cell transplantation (HSCT). The validated LC-MS/MS method is linear over wide concentration ranges (125–2000 ng/mL), accurate, and reproducible in the absence of matrix effects, allowing for the specific and rapid quantification of Bu and allowing next-dose recommendations to be made in a timely fashion to answer clinicians’ needs. Given the lack of data on the stability of Bu in real clinical samples, stability was assessed both on quality controls and on real samples to set up a robust protocol in real-life conditions. This novel LC-MS/MS method is suitable for application to the TDM-guided personalization of conditioning treatments with high-dose busulfan in pediatric patients undergoing HSCT.